The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1159/000321345
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Paradigms of Impulsivity and Alcohol Dependence: A Review

Abstract: Impulsivity can be defined as choosing a smaller, immediate reward over a larger, delayed reward. From this perspective, addictive behaviors such as substance abuse and pathological gambling reflect a series of impulsive choices. However, impulsivity is not a homogeneous construct. Laboratory measures of impulsivity reflect two types of processes. The first is related to behavioral inhibition and refers to an individual’s ability to appropriately inhibit thoughts or actions. The second is the delay of reward d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 80 publications
(66 reference statements)
2
33
0
1
Order By: Relevance
“…Important for a determination of a KOR agonist-induced impulsive-like phenotype is the fact that neither omissions nor total response rates were altered in the SSRT by KOR agonist infusions, showing that neither motivation nor locomotion, respectively, were affected by U50,488. These data support the hypothesis that KOR activation can regulate impulsive phenotypes, an effect that was shown to be specific to response inhibition and that supports contemporary assertions that the SSRT paradigm has predictive validity for an alcohol-dependent state (Aragues et al, 2011). The present results also increase confidence in the construct validity of 'mimicking' an alcohol-dependent withdrawal state using KOR agonist infusions (Berger et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Important for a determination of a KOR agonist-induced impulsive-like phenotype is the fact that neither omissions nor total response rates were altered in the SSRT by KOR agonist infusions, showing that neither motivation nor locomotion, respectively, were affected by U50,488. These data support the hypothesis that KOR activation can regulate impulsive phenotypes, an effect that was shown to be specific to response inhibition and that supports contemporary assertions that the SSRT paradigm has predictive validity for an alcohol-dependent state (Aragues et al, 2011). The present results also increase confidence in the construct validity of 'mimicking' an alcohol-dependent withdrawal state using KOR agonist infusions (Berger et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…The interest lies in the apparent U50,488-mediated hedonic-like behavioral overlap with impulsive-like behavior and the fact that PDYN, DYN A and B and OPRK1 are upregulated in brain regions not only heavily implicated in the cognitive control of decision-making and impulse control (Crews and Boettiger, 2009;Bazov et al, 2013;Winstanley, 2007), but also as integrators of affect and decision-making (Aragues et al, 2011), suggesting a novel PFC/OFC-based DYN/KOR target for therapeutics to treat impulse-control symptoms in dependence and possibly other neuropsychiatric disorders. The fact that nor-BNI did not reduce levels of impulsivity beyond baseline levels suggests that KOR ligands should show utility in treating conditions of reduced impulse control involving a dysregulated DYN/KOR system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impulsivity reflects the balance of two independent behavioral processes: 1) approach or activation associated with reinforcement and 2) inhibition associated with punishment, with impulsive individuals exhibiting hyperactivation or hypoinhibition (e.g., Bechara, 2005). Neuroimaging studies have confirmed the interplay between reinforcement pathways (ventral striatum/nucleus accumbens and orbitofrontal, dorsal, and lateral regions of the prefrontal cortex) and inhibitory pathways (amygdala, insula, anterior cingulate, right inferior frontal gyrus, subthalamic nucleus, and supplementary motor areas of the prefrontal cortex) associated with impulsivity and drug abuse vulnerability (Nigg et al, 2006;Aragues et al, 2011;Dalley et al, 2011;Hommer et al, 2011). Impulsive individuals, determined using either personality-or performance-based criteria, initiate drug use at earlier ages, escalate to heavy use, and transition to abuse and dependence more quickly and are less likely to remain abstinent after treatment compared with nonimpulsive individuals (de Wit, 2009;Dick et al, 2010;Dalley et al, 2011).…”
Section: A Individual Differencesmentioning
confidence: 99%
“…La impulsividad, la búsque-da de sensaciones, el autoconcepto y la conducta antisocial se encuentran entre los factores de riesgo para el uso de sustancias adictivas en los adolescentes (Llorens et al, 2005). La impulsividad y la desinhibición son los factores más consistentemente relacionados con el comportamiento de consumo de alcohol (Aragues, Jurado, Quinto, y Rubio, 2011). Además, la impulsividad se relaciona con la cantidad de alcohol ingerido (Cortés, Giménez, Motos, y Cadaveira, 2014) y, durante la adolescencia, predice un patrón de abuso de alcohol en la edad adulta (Chassin, Flora, y King, 2004).…”
Section: El Manual Diagnóstico Y Estadístico De Los Trastornos Mentunclassified